Mobility and sociality in proximity-sensitive digital urban ecologies: 'Timid encounters' and 'seam-sensitive walks'. (14th March 2016) - Licoppe, Christian; Inada, Yoriko
Abstract : This paper is a case study of the use of a proximity-sensitive game played on mobile gaming terminals, in Japan and in France, Dragon Quest 9, and of distinctive forms of mobility and urban encounters which emerge around it. We show how players, when assembled together, walk the 'connected walk, ' that is they adopt a particular gait, slower than the usual walking pace, with repeated pauses which appears as a tentative and exploratory kind of mobility oriented towards the random occurrence of proximity-based screen-mediated events, and therefore both adjusted to and constitutive of the proximity-sensitive hybrid ecology as a serendipitous place, to be experienced as such. With respect to urban encounters, we have identified a characteristic tension, relevant to locative media in general, in which concerns with potential identification and recognition 'in the game' contrasts with the interaction order of urban traffic encounters, characterized by 'civil inattention.' This gives rise to the phenomenon of 'timid encounters, ' in which players strive to experience game encounters with other players a few meters away, while trying to elude visual or verbal recognition.